Integration of Primary Health Care Services at Puskesmas in East Pekalongan Sub-district with a Formative Evaluation Approach - Teguh Irawan; Jaya Maulana; Siwi Sri Widhowati; Arni Zulfa Laila (PT. Anagata Sembagi Education, 2025)
Primary care integration (ILP) is a pillar of health transformation to strengthen primary health care by bringing health services closer to the village level, targeting the entire life cycle, and strengthening local area monitoring (PWS). The purpose of the study was to analyze the implementation of Primary Care Integration (ILP) at Puskesmas in East Pekalongan District. The research method used qualitative analysis with a case study approach. Data collection was carried out at the Puskesmas in the East Pekalongan sub-district of Pekalongan City. Data collection with in-depth interviews involving 20 informants and data processing using thematic analysis with CIPP variables. This study found that in the context aspect, the goal has not been achieved optimally to bring health services closer and expand due to the lack of cadres, influential factors are family support and officer involvement and infrastructure, targeting the entire life cycle. In the input aspect, human resources are not sufficient, especially medical personnel and cadres for many targets, funding is insufficient for activities, infrastructure for tools is sufficient but the place of implementation is still not large enough and health test kits are still lacking. In the process aspect, planning has gone well, organizing is well structured, it's just that the number of cadres and health workers is still lacking to serve all life cycles, for Pekalsanaan it is still running as much as possible and for evaluation it still refers to the old mechanism and for evaluations carried out regularly every month. In the product aspect, the results of activities can increase the level of visits and the community becomes more enthusiastic in participating in the ILP posyandu.